Respuesta :

Answer is: 4x^6y

x^4•x^2=x^4+2=x^6

Answer:

Not B,   A or C    I believe it is C

Step-by-step explanation:

x^4y and 4x^2

(x^4×y)×(4x²)  =   (yx^4)(4x²)     =   = 4× y × x^4 × x²    =  4yx^6  

exponents of the same base add

lets try this with REAL numbers to check the answer let x = 2 and y =3

(yx^4)(4x²)     =    (3×2^4)(4×2²)  =  (3×16)(4×4)  = 48×16  =  768

4yx^6   =    4(3)(2³)(2³)

           =     12(8)(8)

          =     768  

the following is also an answer if I replace the 4 with x²        

yx^8    =   3×2^8   =    3×(2×2×2×2×2×2×2×2)              

                             =    3×(2×2×2×2)×(2×2×2×2)      

                             =    3×(2^4)×(2^4)

                             =    3×16×16

                             =    3 × 256

                             =    768                  These calculations are the same

ACCESS MORE